Strategies to Improve the Performance of Medical Record Officers Through Structural Equation Model Analysis - Tawil, Muhamad Risal; Anita, Anita; Leo, Muarif; Kuswinton, Kuswinton; Teheni, Muhammad Tasjidin; Fatmala, Wilda; Sinta, Niska Salsiani; Rongre, Yohanis (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
This study intends to develop a performance model for hospital medical staff by analyzing the influence of work meaning and servant leadership on job performance, as well as testing the mediation role of employee gratitude and work engagement, including measuring the impact of all variables if tested simultaneously. Some previous empirical studies have stated that servant leadership has a 67% effect on improving employee performance, but other studies show the opposite. The respondents of this study were 323 medical record officers from private hospitals in Makassar City. This study uses a factorial correlation design that was tested using the Statistical Program for Social Science (SPSS) and Analysis of Moment Structure (AMOS) version 22. The study results show that employee gratitude significantly strengthens the relationship between servant leadership and job performance. In addition, work engagement has proven to be a suitable catalyst for the relationship between meaningful work and job performance. Developing dimensions and indicators of servant leadership, meaningful work, employee gratitude, work engagement, and job performance from the perspective of employee interaction with the organization is valuable in strengthening social exchange theory in the health sector. This study also suggests that hospital management should always maintain employee gratitude and employee work engagement as an effective strategy for improving the performance of hospital medical record officers.